Hydrothermal Synthesis of Nanomaterials - Gan, Y. X.; Jayatissa, A. H.; Yu, Z.; Chen, X.; Li, M.
Hydrothermal synthesis is one of the most commonly used methods for preparation of nanomaterials. It is basically a solution reaction-based approach. In hydrothermal synthesis, the formation of nanomaterials can happen in a wide temperature range from room temperature to very high temperatures. To control the morphology of the materials to be prepared, either low-pressure or high-pressure conditions can be used depending on the vapor pressure of the main composition in the reaction. Many types of nanomaterials have been successfully synthesized by the use of this approach. There are significant advantages of hydrothermal synthesis method over others. Hydrothermal synthesis can generate nanomaterials which are not stable at elevated temperatures. Nanomaterials with high vapor pressures can be produced by the hydrothermal method with minimum loss of materials. The compositions of nanomaterials to be synthesized can be well controlled in hydrothermal synthesis through liquid phase or multiphase chemical reactions. This special issue serves as a forum presenting the recent research results of hydrothermal synthesis of nanomaterials. Several papers on hydrothermal synthesis of nanoparticles, nanorods, nanotubes, hollow nanospheres, and graphene nanosheets have been published in this special issue. New synthesis methods, for example, microwave-assisted hydrothermal synthesis and template-free self-assembling catalytic synthesis, are reported in this special issue. Research work on optimization of the synthesis conditions is included as well. Nanomaterials for applications such as energy harvesting and biosensing are also studied in the papers published in this special issue. In addition, hydrothermal synthesis using waste materials to achieve environment protection was studied in one of the papers. A brief summary of all the eleven accepted papers is presented as follows.
Keywords: HYDROTHERMAL; SYNTHESIS; NANOMATERIALS